2006
DOI: 10.1016/j.bbrc.2006.09.124
|View full text |Cite
|
Sign up to set email alerts
|

Zuotin, a DnaJ molecular chaperone, stimulates cap-independent translation in yeast

Abstract: A small inhibitor RNA (IRNA) isolated from yeast has previously been shown to efficiently block poliovirus and hepatitis C virus IRES-mediated translation by sequestering mammalian RNA-binding (transacting) factors that play important roles in cap-independent translation. Here we have investigated the IRNA-binding proteins that might be involved in cap-independent translation in the yeast Saccharomyces cerevisiae. We have identified Zuotin, a DnaJ chaperone protein similar to mammalian HSP-40 chaperone, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…NS5A has previously been reported to alter HCV IRES‐mediated translation,24, 25 and a HSP40 family member has been implicated in IRES‐dependent translation in yeast 26. To determine whether HSP40 and HSP70 were involved with NS5A alteration of IRES activity, we used a cell culture–based bicistronic reporter system (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NS5A has previously been reported to alter HCV IRES‐mediated translation,24, 25 and a HSP40 family member has been implicated in IRES‐dependent translation in yeast 26. To determine whether HSP40 and HSP70 were involved with NS5A alteration of IRES activity, we used a cell culture–based bicistronic reporter system (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HSP70 is implicated in NS5A‐mediated IRES translation, as demonstrated by decreased IRES activity with HSP70 knockdown in the IRES reporter system. A yeast HSP40 homolog, and indirectly HSP70 by virtue of their existence as a complex, have previously been shown to be important for cellular IRES specific translation in yeast 26. The reduction in the IRES activity with knockdown of HSP40 is minimal, and with HSP70 is modest compared with Quercetin treatment and may be related to several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the HAP4, YAP1, and TAF145 elements were identified based on the ability of translationally competent yeast extracts to conduct internal initiation on these mRNAs. Since the identification of these elements, they have all been shown to be active in living cells (13,19,20). Of the aforementioned list of yeast cellular IRES elements, only the TIF4631 IRES has been defined by deletion analysis, but no structural data exists for the minimal IRES element (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, purified Zuo1 unspecifically interacts with a variety of nucleic acids. Initially, Zuo1 was identified via its ability to interact with Z-DNA (Zhang et al, 1992), it also interacts tightly with tRNA (Wilhelm et al, 1994) and recently was shown to bind to a small inhibitor RNA (Raychaudhuri et al, 2006). The mouse homolog MIDA1 interacts with DNA that forms small stem loop structures (Inoue et al, 2000).…”
Section: Introductionmentioning
confidence: 99%